2009
DOI: 10.1111/j.1365-2982.2009.01361.x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding measurements of intestinal permeability in healthy humans with urine lactulose and mannitol excretion

Abstract: Our aim was to understand the information from differential two-sugar excretion (2-SE) in measuring intestinal permeability. In a crossover study in 12 healthy volunteers, we compared urinary excretion ratios of lactulose (L) to mannitol [(M) LMR] after ingestion in liquid formulation (LF) or in delayed-release, methacrylate-coated capsules (CAP). Both formulations were radiolabeled. Urine was collected every 2 hours from 0-8h, and from 8-24h. Two hours after LF, gastric residual was 15.9 ± 6.2 % (SEM), and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
146
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(159 citation statements)
references
References 27 publications
(30 reference statements)
6
146
2
Order By: Relevance
“…This approach allowed quantification of all sugar probes of interest in both urine and plasma in one run, with a detection limit of 0.05 mol/L for disaccharides and 0.10 mol/L for monosaccharides. These lower limits of detection are significantly lower than previously reported [17,18], including a recent report of Camilleri et al who found detection limits of 4.98 mol/L (1.7 g/mL) for disaccharide lactulose and 1.92 mol/L (0.035 g/mL) for monosaccharide mannitol using normal phase LC-MS for permeability analysis in urine [18]. In our study, the increased analytic sensitivity allowed a 5-fold reduction of the oral lactulose dose.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…This approach allowed quantification of all sugar probes of interest in both urine and plasma in one run, with a detection limit of 0.05 mol/L for disaccharides and 0.10 mol/L for monosaccharides. These lower limits of detection are significantly lower than previously reported [17,18], including a recent report of Camilleri et al who found detection limits of 4.98 mol/L (1.7 g/mL) for disaccharide lactulose and 1.92 mol/L (0.035 g/mL) for monosaccharide mannitol using normal phase LC-MS for permeability analysis in urine [18]. In our study, the increased analytic sensitivity allowed a 5-fold reduction of the oral lactulose dose.…”
Section: Discussioncontrasting
confidence: 58%
“…The disaccharide sucralose and the sugar alcohol erythritol are not degraded by human colonic bacteria [20,21], allowing their use as markers of colonic and total GI permeability. Alternatively, assessment of samples (either urine or plasma) collected more frequently than the classical 0-5 h urinary collection, might reflect permeability of specific parts of the gastrointestinal tract [18]. Considering that sugar probes first appear in plasma after permeation through the mucosal epithelium, we aimed to perform plasma-based permeability analysis next to the classical urinary approach.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from this last line of defence, the mucus layer covering the intestinal mucosa as well as the gut microbiota and products from the immune system (such as defensins and secreted antibodies) have important roles in maintaining gut integrity. 135 Between 12% and 50% of patients with IBS have been reported to have altered intestinal permeability in research studies 136 using various methods to reflect gut permeability at different parts of the gastrointestinal tract, [137][138][139] and both postinfectious IBS as well as nonselected groups of patients with IBS have been investigated. An acute bacterial infection results in a transient increase in intestinal permeability.…”
Section: Barrier Functionmentioning
confidence: 99%
“…The importance of %LMR as marker of IP in different GI diseases has already been highlighted by different studies utilizing different procedures [9]. In this framework, to our knowledge, this is the first study comparing the HPAEC-PAD with ESAT.…”
Section: Probementioning
confidence: 94%